The Application of Text Compression to Short Message Service Using Huffman Table - Ahmad Affandi; Saparudin Saparudin; Erwin Erwin (Generic, 2011)
Short Message Service (SMS) is a way of sending short messages in a quick and relatively cheap price. However, besides easiness provided, these SMSs limit the number of characters that can be sent by users. A message sent via SMS, has a maximum capacity of 140 bytes. This causes a person who wants to send a message long enough, consists of a number of characters will have difficulty. Although it is delivered, the message must be assembled into a number of SMS based on maximum capacity. Several ways can be performed to overcome this, one of them by doing compression. By using Huffman table an application text compression on SMS is made in order to compress and decompress when sending and receiving message. This application is made by J2ME and will run on mobile phones based on MIDP 2.0. The results of this study SMS text compression application with Huffman table overall is able to perform the compression process of an SMS text with an average compression ratio of 28.73%.